Analysis Level of Understanding of Online Learning Results in the Subject of Administration at Vocational School Negeri 57 Jakarta - Mahdavikia, Aldhara; Setiawati, Tati; Nurani, Atat Siti (Media Pendidikan Gizi dan Kuliner, 2024)
Online learning has become a popular solution for teaching and learning during the COVID-19 pandemic. This study aims to measure students' understanding of food and beverage planning in KD, focusing on the food and average services. The research method used is a survey with tests as a tool to collect data. The study involved 85 students from Class XI TB at SMK Negeri 57 Jakarta, determined by simple random sampling. The results showed that the students had the lowest understanding factor of food and average services and the highest understanding factor of food and average service procedures. The level of understanding of student learning outcomes was in the Extrapolation category. The study concluded that the level of understanding of food and average services in the dining class XI students of SMK Negeri 57 Jakarta is in a fairly good category.